Removal of inorganic species from mallee biomass and biochars by water leaching - Yip, Kong; Li, Chun-Zhu; Wu, Hongwei (ICMS Pty Ltd, 2010)
This study reports the removal of inorganic species by water leaching from a Western Australia mallee biomass and its biochars. The study focuses on the removal of AAEM species (Na, K, Ca and Mg) and other nutrient elements (Cl, S, P and N). The biochars were produced from slow-heating pyrolysis of various mallee components (wood, leaf and bark) at different temperatures. Most of the AAEM species and P were retained in the biochars following pyrolysis (implying insignificant volatilisation of these species during pyrolysis), while S, P and Cl were volatilised to different extents during pyrolysis. Water leaching was carried out on the biomass and biochars until the contents of the inorganic species in the leached sample reached equilibrium.The results have shown that the ash yield of the various samples can be reduced considerably by water leaching in most cases. Na, K, and Cl were leached out significantly. Varying degrees of removal of other nutrients (Ca, Mg, S and P) were also achieved, depending on biomass component and the pyrolysis temperature. The removal of different inorganic species at different pyrolysis temperatures are discussed in terms of the possible forms of the inorganic species existing in the biomass as well as their transformation during pyrolysis. The present findings have significant implications on the utilisation of the biomass as a fuel and on soil applications of the biochar.